(untitled) (Archive of Conferences, 2022)
The following article provides some findings about linguostatistic features of English and Uzbek proverbs about badness.Proverbs, which are one of the genres of folklore, combine the life experiences, dreams and aspirations of ancestors, their attitude to the state and society, historical and spiritual state, philosophical, ethnic and aesthetic feelings. They have been polished over the millennium to form a concise poetic form. Linguistic statistics is a branch of linguistics that is used to study, analyze, and classify language sources using a statistical method. Linguostatistical research has revealed some similarities and stark differences between English and Uzbek folk proverbs.